Building a Department Community: Connecting with Faculty - Kathleen Everts Danielson (Academic Chairpersons Conference Proceedings, 2023)
Participants will learn about building a community within a department to build connections with and among faculty, including strategies for communication, appreciation, and interactive faculty meetings, as well as mentoring suggestions for new faculty.
Keywords: Community Connection Communication Appreciation Mentoring